PENGARUH LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA POLITEKNIK CAHAYA SURYA KEDIRI - Petty petty Arisanti; Rini Ratna Nafita Sari (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2020)
This research was conducted with the aim of finding out whether the family environment has a strong influence on the interest in entrepreneurship in Accounting Study Program students class 2017-2018, Cahaya Surya Kediri Polytechnic. This research method is a quantitative research method of data collection using an observation questionnaire and strengthened using interview techniques. The family environment, especially parents, plays an important role in influencing interest in work for children in the future, including in entrepreneurship. Parents who are entrepreneurial in certain fields can generate interest in entrepreneurship in other words to continue the business because they do not start from scratch, just continue. The interest in entrepreneurship in the Accounting Study Program students class of 2017-2018 Polytechnic Cahaya Surya Kediri is seen from internal factors that are quite high. This is evidenced by the fact that most students have online businesses that have been running in recent years and are driven by family factors which in fact have a business and other factors, namely the current sophistication of technology that is completely online, young people, especially students, can easily market a product to various places and circles without having to have their own place of business.